Penerapan Hukum terhadap Menerbangkan Balon Udara dalam Rangka Melakukan Tradisi Adat - Dina Fahira Azhari Siregar; Marlina Marlina; Fajar Khaify Rizky (Wajah Hukum, 2026)
Flying hot air balloons in East Javanese society is a custom before welcoming Eid al-Fitr, but in this case, this custom has the potential to be dangerous to public safety. The case of flying a hot air balloon that endangers an aircraft that will be studied in this research is a case of a hot air balloon flown by several people and is considered a criminal offense as has permanent legal force based on Court Decision Number 68 / PID.B / 2022 / PN Png and Decision Number 114 / Pid.B / 2022 / PN Mjy. The research method uses a normative method. The results of the study state that the legal regulation of flying hot air balloons within the framework of traditional traditions in Indonesia is regulated in the Minister of Transportation Regulation Number 40 of 2018, however, as the regulation is a ministerial regulation, its substance is limited to regulating the procedures for supervision and administration in flying hot air balloons. The qualifications for criminal acts that endanger aviation are according to Law Number 1 of 2009 concerning Aviation. As seen from Article 411 of the Law, it does not explicitly mention criminal provisions for the actions of people who fly hot air balloons. The judge's consideration in applying Article 411 in Decision Number 68/Pid.B/2022/PN Png and Decision Number 114/Pid.B/2022/PN Mjy considered that the defendants had endangered the flight by flying the hot air balloon.